(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to observe the effect of Ziziphus spina-christi extract against anxiety related behavior induced by scopolamine. Rats were randomly divided into six groups, each group consists of eight rats. Vehicle group received distilled water, negative control received scopolamine (1 mg/kg) and positive control received diazepam (1 mg/mL). Experimental groups received Z. spina-christi extract (50, 100 and 200 mg/kg IP) 30 min after scopolamine injection. Anxiety related behaviors were assessed using the elevated plus maze. The rotarod test was used to evaluate motor coordination. Administration of Z. spina-christi extract (200 mg/kg) significantly increased the time spent in the open arm of elevated plus maze. The extract also reduced the percentage of closed arms entries and time spent in the closed arms. Different concentration of Z. spina-christi extract didnt affect motor coordination and balance. Hydro-alcoholic extract of Z. spina-christi significantly ameliorate scopolamine-induced anxiety. Video Clip of Methodology: Elevated plus maze: 1 min 58 sec Full Screen Alternate